2018
DOI: 10.5664/jcsm.7538
|View full text |Cite
|
Sign up to set email alerts
|

Oximetry as an Accurate Tool for Identifying Moderate to Severe Sleep Apnea in Patients With Acute Stroke

Abstract: Study Objectives: Sleep-disordered breathing (SDB) is highly prevalent in patients with acute stroke. SDB is often underdiagnosed and associated with neurological deterioration and stroke recurrence. Polysomnography or home sleep apnea testing (HSAT) is typically used as the diagnostic modality; however, it may not be feasible to use regularly in patients with acute stroke. We investigated the predictive performance of pulse oximetry, a simpler alternative, to identify SDB. Methods: The records of 254 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…In contrast, pulse oximeters are simple and useful screening tools. 18 Overnight pulse oximetry is generally satisfactory in detecting moderate to severe OSA, 28,29 but it has limited sensitivity for detecting mild OSA. The ODI is usually the most effective measure for a diagnosis of OSA, and cutoffs of 5.0, 10.0 or 15.0 are applied on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pulse oximeters are simple and useful screening tools. 18 Overnight pulse oximetry is generally satisfactory in detecting moderate to severe OSA, 28,29 but it has limited sensitivity for detecting mild OSA. The ODI is usually the most effective measure for a diagnosis of OSA, and cutoffs of 5.0, 10.0 or 15.0 are applied on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies compared AHI and ODI from the same recordings, with correlation coefficients reported to range between 0.745 and 0.97 [ 14 , 15 , 16 , 17 , 18 , 19 ]. Some studies compared simultaneously performed oximetry and PSG, with correlation coefficients reported to be 0.617–0.95 [ 20 , 21 ], while others independently performed oximetry and PSG [ 23 , 24 ], with correlation coefficients of 0.6 and 0.62.…”
Section: Discussionmentioning
confidence: 99%
“…First, the oximetry ODI was not measured simultaneously with PSG/OCST. Comparisons of ODI and AHI/REI from the same recordings showed the best correlation [ 14 , 15 , 16 , 17 , 18 , 19 ] ( Figure 5 ), followed by simultaneous recording by different devices [ 20 , 21 , 25 ]. The correlation was worst when comparing ODI and AHI/REI from different devices on different nights [ 23 , 24 ] ( Figure 2 a and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Oximetry is another less expensive and easier alternative that is widely available. 8,9 However, attaching a device to the finger during sleep is uncomfortable and may limit natural position change during sleep; moreover, the device is removed on waking up, which limits its use in multiday, continuous recordings.…”
Section: Introductionmentioning
confidence: 99%